HOT COMPRESSED WATER EXTRACTION OF CRUDE PALM OIL FROM PALM MESOCARP - Mohd. Sharizan Md. Sarip, 1985-, author; Noor Azian Morad, Prof.Dr., supervisor; Yamashita, Yoshiyuki, Prof.Dr., supervisor; Tsuji, Tomaya, Prof.Dr., supervisor; Institut Teknologi Antarabangsa Malaysia - Jepun (Kuala Lumpur : Universiti Teknologi Malaysia, 2016)
Thesis (PhD)